PERANAN ADVOKAT DALAM MEWUJUDKAN KEWENANGAN PENGADILAN AGAMA DALAM BIDANG KEWARISAN - Mohammad Ramli (LP2M IAI Miftahul Ulum Pamekasan, 2019)
In matters of inheritance between religious people, Islam has determined in the Law which establishes the authority of the Court. This authority has been approved in a limited way in the Religious Court Law. The problem that often occurs is that the advocate as the attorney of the plaintiff (client) does not follow the provisions submitted and submitted to the District Court on the basis of Unlawful Acts. In general, clients do not know about the endorsement. When this happens, the role of the advocate will be canceled by the role of the religious court and deciding the case of inheritance between Muslims (Islamic personaliatas)